Deformation parameters of hypertrophied left ventricular myocardium in arterial hypertension - B. Amarzhargal; N. F. Beresten; S. B. Tkachenko (Кардиоваскулярная терапия и профилактика)
Aim. To assess deformation characteristics of normal left ventricular (LV) myocardium and hypertrophied LV myocardium in arterial hypertension (AH) patients, using tissue Doppler examination of LV lateral wall and interventricular septum (IVS).Material and methods. In total, 30 healthy subjects from the control group (CG) and 80 AH patients were examined: Group I (n=40) with moderate LV hypertrophy (LVН), Group II (n=40) with severe LVН.Results. Systolic and early diastolic strain rates (SRsys, SRe) in Group II patients were significantly reduced for middle and apical IVS segments, comparing to the controls. The difference between Groups I and II was manifested in decreased SRe for basal IVS segment and lateral LV wall. The analysis of isovolumic contraction and relaxation time on SR graphs demonstrated a two-phase structure in healthy controls and AH patients with LVН. The duration of prolonged phase of isovolumic contraction (IVC) and negative phase of isovolumic relaxation (IVR) depended on LVН severity. There was a significant association between LVН parameters and deformation parameters of LV myocardium.Conclusion. There was an association between LVН and deformation parameters of LV myocardium (SR, ε). In AH patients, increased dynamic activity of left atrium was associated with disturbed relaxation of hypertrophied LV myocardium. The duration of positive IVC component and negative IVR component on SR graphs was longer in higher LV myocardial mass index (LV MMI), especially for middle LV segments. Increase in LV MMI correlated with decrease in segmental LV myocardium deformation. Positive association between systolic deformation, LVH severity, systolic blood pressure, and diastolic LV wall thickness was observed.